A dual-task-embedded virtual reality system for intelligent quantitative assessment of cognitive processing speed - Zhou, Yuzhao; Zhao, Yixuan; Xiang, Zirui; Yan, Zhixin; Shu, Lin; Xu, Xiangmin; Zhang, Lulu; Tian, Xiang (Frontiers in Human Neuroscience, 2023)
Processing speed is defined as the ability to quickly process information, which is generally considered as one of the affected cognitive functions of multiple sclerosis and schizophrenia. Paper–pencil type tests are traditionally used in the assessment of processing speed. However, these tests generally need to be conducted under the guidance of clinicians in a specific environment, which limits their application in cognitive assessment or training in daily life. Therefore, this paper proposed an intelligent evaluation method of processing speed to assist clinicians in diagnosis. We created an immersive virtual street embedded with Stroop task(VR-Street). The behavior and performance information was obtained by performing the dual-task of street-crossing and Stroop, and the intelligent evaluation model was developed using machine learning. A 50-participant dataset was established with the label of standard scale. The estimated results showed that the proposed method can estimate the processing speed score with an adequate accuracy (mean absolute error of 0.800, relative accuracy of 0.916 and correlation coefficient of 0.804). The combination of Stroop features and behavior features showed better performance than single task features. The proposed method provides a new opportunity for accurate quantitative evaluation of cognitive function through virtual reality.